2018
DOI: 10.33584/jnzg.2018.80.334
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of bioactive compounds in Plantago lanceolata is genotype specific

Abstract: Plantain (Plantago lanceolata) is known to contain bioactive compounds including verbascoside (acteoside), aucubin and catalpol. Limited New Zealand data are available to quantify the concentrations of secondary plant compounds in cultivars of plantain. This experiment compared secondary plant compound concentrations for five cultivars or breeding lines of plantain and the botanical distribution of these compounds over a year. For all cultivars verbascoside concentration was greatest, aucubin intermediate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Total herbage dry matter yields of bars with the same letters are not significantly different (p > 0.05). N. However, several studies showed that secondary metabolites with BNI capacity are produced by plantain and are present in above ground biomass and roots (Marak et al 2000;De Deyn et al 2009;Dietz et al 2013;Miehe-Steier et al 2015;Box and Judson 2018). Box and Judson (2018) reported for the plantain var.…”
Section: Mesocosm Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total herbage dry matter yields of bars with the same letters are not significantly different (p > 0.05). N. However, several studies showed that secondary metabolites with BNI capacity are produced by plantain and are present in above ground biomass and roots (Marak et al 2000;De Deyn et al 2009;Dietz et al 2013;Miehe-Steier et al 2015;Box and Judson 2018). Box and Judson (2018) reported for the plantain var.…”
Section: Mesocosm Experimentsmentioning
confidence: 99%
“…N. However, several studies showed that secondary metabolites with BNI capacity are produced by plantain and are present in above ground biomass and roots (Marak et al 2000;De Deyn et al 2009;Dietz et al 2013;Miehe-Steier et al 2015;Box and Judson 2018). Box and Judson (2018) reported for the plantain var. 'Hercules', used in our experiments, mean leaf concentrations of 39.1 mg g −1 DM verbascoside, 39.1 mg g −1 DM aucubin and <5 mg g −1 DM catalpol over a year on a silt loam soil in New Zealand.…”
Section: Mesocosm Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms driving increased diuresis by sheep fed both plantain breeding lines and "Ecotains" are unclear, but may be related to the presence of secondary compounds in the feed. The presence of secondary plant compounds in plantain herbage is genotype specific (Al-Mamun et al 2008;Box & Judson 2018) providing a possible explanation for the differences in urine volume among the genotypes evaluated here. These results suggest that selection of specific plantain genotypes may reduce urinary N concentration by increasing urine volume thereby diluting urinary N, and reducing the risk of N leaching from grazing systems.…”
Section: Diuretic Potencymentioning
confidence: 81%
“…Finally, significant differences in nitrate produced in soil microcosms treated with urine from sheep grazing different PL cultivars have been observed, particularly in the early phase of the incubation (Fraser et al, 2018; Peterson et al, 2023b; Figure 2). These differences are thought to be related to the concentrations of bioactive compounds in the leaf material at the time of consumption, which are known to vary with cultivar and season (Box & Judson, 2018). The compounds responsible for this urine‐derived inhibition, along with the mechanism by which they delay nitrification are yet to be confirmed.…”
Section: Soil N Processingmentioning
confidence: 99%